Persepsi Pemustaka terhadap Layanan Sirkulasi di Dinas Kearsipan dan Perpustakaan Kabupaten Pesisir Selatan - Jannah, Mifthahul; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The purpose of this study to determine how the perception of liustors to the attitude of librarians in providing services in the Library Service and Library Archives South Coast District. Data were collected by distributing questionnaires to library visitors. Samples taken as many as 41 respondents. The result of questionnaire was prepared by recapitulation of research result. Based on the results of the study concluded as follows: 1) In the process of membership registration, as many as 69% agreed about the fast in the process of registration 2) In the circulation process there, as many as 80% agreed about easy in doing the circulation . 3) In the librarian's attitude to give service 58% states do not agree mengalam librarian assist in the process of searching collection at Department Archives and Library of Pesisir Selatan Regency.Keywords: attitude, librarian, perception, reader.